Long Passage Times of Short ssDNA Molecules through Metallized Nanopores Fabricated by Controlled Breakdown. (13th October 2014) - Kwok, Harold; Waugh, Matthew; Bustamante, José; Briggs, Kyle; Tabard‐Cossa, Vincent
<x xml:space="preserve">Abstract</x> The fabrication of individual nanopores in metallized dielectric membranes using controlled breakdown directly in solution is described. Nanopores as small as 1.5‐nm in diameter are fabricated in Au‐coated silicon nitride membranes immersed in 1 m KCl by subjecting them to high electric fields. The physical and electrical characteristics of nanopores produced with this method are presented. The translocation of short single‐stranded DNA molecules is demonstrated through such nanopore devices without further passivation of the metallic surface. Metallized nanopores can prolong the translocation times of 50‐nt ssDNA fragments by as much as two orders of magnitude, while the slowest events can reach an average speed as slow as 2 nucleotides per millisecond. The mechanism for the long dwell‐time distribution is differentiated from prior studies, which relied on friction to slow down DNA, and is attributed to nucleotide‐Au interactions.